2021
DOI: 10.5195/rt.2021.777
|View full text |Cite
|
Sign up to set email alerts
|

Reality check: How adolescents use TikTok as a digital backchanneling medium to speak back against institutional discourses of school(ing)

Abstract: This article centers on how TikTok’s adolescent users “speak back” to discourses of school(ing) in the US.  Through a discussion of four viral, school-related trends that have proliferated on TikTok over the past two years, the author calls attention to the ways school(ing), as a largescale, democratic project and socially constructed phenomenon, is being shaped by young people, for young people on a digital platform that backchannels a largely resistant attitude toward the institutional framing of school(ing)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 8 publications
1
7
0
1
Order By: Relevance
“…In summary, the TeachTokerists enumerated that TikTok may subject students to videos with adult contents, profane language, excessive app use, unreliable information, and criticisms from other users. Although these were the shared perceptions of TeachTokerists in the Philippines as participants in this study, various researchers appear to have yielded similar findings (Anderson, 2020;Jaffar et al, 2019;Liang, 2021;Vijay & Gekker, 2021;Wright, 2021).…”
Section: Educational Materialssupporting
confidence: 66%
See 1 more Smart Citation
“…In summary, the TeachTokerists enumerated that TikTok may subject students to videos with adult contents, profane language, excessive app use, unreliable information, and criticisms from other users. Although these were the shared perceptions of TeachTokerists in the Philippines as participants in this study, various researchers appear to have yielded similar findings (Anderson, 2020;Jaffar et al, 2019;Liang, 2021;Vijay & Gekker, 2021;Wright, 2021).…”
Section: Educational Materialssupporting
confidence: 66%
“…Despite TikTok's proven track record, it is also peppered with cons. TikTok is viewed as a distraction, a bad influence, and a stumbling barrier in students' path to self-improvement (Liang, 2021;Wright, 2021). The study of Vijay and Gekker (2021) has raised concerns about controversial materials, hate speeches, and a lack of platform responsibility.…”
Section: Introductionmentioning
confidence: 99%
“…Snapchat involves the setting up of contacts as groups of users who communicate with each other whereas TikTok is not based on followers rather it uses an algorithm to ‘provide endless access to videos that TikTok believes the user would like’ 29 . TikTok's ease of use and vibrancy with a stream of videos on screen upon opening the app, even without having signed onto the app, provides an ‘instantaneous participatory mediascape’ 30 …”
Section: Discussionmentioning
confidence: 99%
“…Building trust and demonstrating care were of paramount importance to this study's participants. Douglas and Jackson 38 found that at‐risk young people were motivated by their own lived experience to help or mentor other at‐risk young people, which could lead to prosocial behaviours 20,28–30 …”
Section: Discussionmentioning
confidence: 99%
“…This application had 100 million users and a potential audience of 1 billion when it first launched, back when it was still known as Douyin [8,9]. Due to the individual's success in creating videos, there were TikTok celebrities even in Indonesia [10][11][12]. This platform promotes the Challenge as a draw for users to want to utilize TikTok [13].…”
Section: Literature Reviewmentioning
confidence: 99%